Photostability of oxazoline RNA-precursors in UV-rich prebiotic environments. Issue 95 (14th November 2018) - Janicki, Mikołaj J.; Roberts, Samuel J.; Šponer, Jiří; Powner, Matthew W.; Góra, Robert W.; Szabla, Rafał
Abstract : Oxazoline precursors of RNA nucleosides are highly photostable molecules and could survive long-term UV-irradiation on the early Earth. Abstract : Pentose aminooxazolines and oxazolidinone thiones are considered as the key precursors which could have enabled the formation of RNA nucleotides under the conditions of early Earth. UV-irradiation experiments and quantum-chemical calculations demonstrate that these compounds are remarkably photostable and could accumulate over long periods of time in UV-rich prebiotic environments to undergo stereoisomeric purification.